Outcomes associated with balloon angioplasty for recurrent coarctation in neonatal univentricular and biventricular norwood‐type aortic arch reconstructions. Issue 7 (6th January 2014) - Whiteside, Wendy; Hirsch‐Romano, Jennifer; Yu, Sunkyung; Pasquali, Sara K.; Armstrong, Aimee
<x xml:space="preserve">Abstract</x> Objectives We evaluated the use of, and outcomes associated with, balloon angioplasty (BA) for recurrent coarctation in single ventricle (SV) and two ventricle (2V) patients following a Norwood‐type aortic arch reconstruction (NTAR). Background Extended patch augmentation of the aorta, a NTAR, is utilized in SV patients undergoing the Norwood procedure (NP) as well as 2V patients with a diffusely hypoplastic aorta. While many studies have evaluated recurrent coarctation following the NP, the incidence of recurrent coarctation and outcomes associated with BA in 2V patients following NTAR are unclear. Methods A retrospective review was performed of all neonates who underwent a NTAR at our institution between 2000 and 2010. The incidence of recurrent coarctation requiring intervention and factors associated with successful BA were evaluated. Results A NTAR was performed in 361 SV patients and 88 2V patients. The incidence of recurrent coarctation requiring intervention was 19.3% in 2V vs. 9.7% in SV patients (P = 0.01) at a median of 0.5 (interquartile range 0.3–1.2) years from initial surgery. BA was successful in 25 SV patients (81%) and 10 2V patients (71%; P = 0.70). Of the characteristics evaluated, lower initial peak‐to‐peak gradient (P = 0.02), larger balloon size for angioplasty (P = 0.02) and larger diameter of the descending aorta (P = 0.01) were associated with BA success. Conclusions Recurrent coarctation following NTAR is more common in 2V patients than in SV patients. BA for recurrent coarctation has similar success in both groups and should continue to be utilized in this population. © 2013 Wiley Periodicals, Inc.